Regionalização da saúde : cartografia dos modos de produção do cuidado e de gestão em saúde - Goya, Neusa (2017)
This study asks questions about the regionalization of health as a strategy to guarantee integrality and universality, principles that are still invisible in the Unified Health System. The general objective was to map knowledge-power relations, which pass through the regionalized modes of production of health care and management. The specific objectives, related to the regionalization of health, were: to problematize its discursive and non-discursive formation; analyse its historical and institutional development in Ceará; to map their process, in the Sobral Region, by the subjective experiences of managers, professionals and users, in health care and management; to analyze the effects of power relations, in the production of institutions, subjectivities and knowledge, for the constitution of the right to health. It was woven by the composition of two research projects, duly approved, and with two layers: State level, on the regionalization of Ceará; Regional level, research in the Sobral Health Region. The theoretical- methodological and analytical ground was that of the cartography allied to Foucaultian archeology. The cartography guided, in Sobral, the landing: in the Regional Interagency Committee; in two specialized ambulatory and two hospital equipments. For production and data collection it used: cartographic writings, such as field diary; observation; interviews and documentary archives. This study interviewed: managers, from the places inhabited and linked to the Secretary of Health of Ceará (14), professionals (11) and users (12) of health equipment. Twenty-three interviews of state managers were added, from the course at the state level. The study updated that the discursive formation of the regionalization of Ceará follows the national normalization, with singular traits, producing it as a reform of the health sector, since the 1990s. A reform that constituted institutions of management, Public Consortium of Health and Social Organization, to manage new regional equipment, polyclinics and hospitals. By these modalities extended the privatization, mercantilization and entrepreneurship of the System. This study also updated the relations of knowledge-power, medical-disciplinary, connecting them to the knowledge-power business-controller, by mechanics such as: clinical protocol linked with management protocols, for efficient health management and care, quality and insurance, given the standardization of serialized behaviors and subjectivities for its handling; dissemination of the contractual form, according to the management modality, specifying the ways of financing the recently deployed specialized services and associating the legal dimension, truth-producing, to the technical-assistance, organizing baskets of restrictive supply of services; use of the hosting and classification of risk, by the exclusive use of biomedical knowledge, justifying the access bottleneck, through the argumentation of life risk. Whereas the link of such mechanisms to the new management modalities, there was the design of 'a new world of health', business model, and 'an old world of health', mirrored in outdated mechanisms and financing, operated by philanthropic management and direct administration. The cartography of the regionalization of health in Ceará, in dialogue with the Sobral Region, has updated this process as a biopolitical invention, marked by the shift from the constitutional ideals to a restricted health production destined to the poorest. But it pointed out the production of escape routes as well, by the meeting between professionals and users, signaling the resistance’s strength and the health system’s micropolitics.